Community perspectives and experiences of quality maternal and newborn care in East New Britain, Papua New Guinea - Alyce N. Wilson; Pele Melepia; Rose Suruka; Priscah Hezeri; Dukduk Kabiu; Delly Babona; Pinip Wapi; Alison Morgan; Joshua P. Vogel; James Beeson; Christopher Morgan; Angela Kelly-Hanku; et al. (BMC, 2023)
Abstract Background Quality maternal and newborn care is essential for improving the health of mothers and babies. Low- and middle-income countries, such as Papua New Guinea (PNG), face many barriers to achieving quality care for all. Efforts to improve the quality of maternal and newborn care must involve community in the design, implementation, and evaluation of initiatives to ensure that interventions are appropriate and relevant for the target community. We aimed to describe community members' perspectives and experiences of maternal and newborn care, and their ideas for improvement in one province, East New Britain, in PNG. Methods We undertook a qualitative descriptive study in partnership with and alongside five local health facilities, health care workers and community members, using a Partnership Defined Quality Approach. We conducted ten focus group discussions with 68 community members (identified through church, market and other community-based groups) in East New Britain PNG to explore perspectives and experiences of maternal and newborn care, identify enablers and barriers to quality care and interventions to improve care. Discussions were transcribed verbatim. A mixed inductive and deductive analysis was conducted including application of the World Health Organisation (WHO) Quality Maternal and Newborn Care framework. Results Using the WHO framework, we present the findings in accordance with the five experience of care domains. We found that the community reported multiple challenges in accessing care and facilities were described as under-staffed and under resourced. Community members emphasised the importance of good communication and competent, caring and respectful healthcare workers. Both women and men expressed a strong desire for companionship during labor and birth. Several changes were suggested by the community that could immediately improve the quality of care. Conclusions Community perspectives and experiences are critical for informing effective and sustainable interventions to improve the quality of maternal and newborn care and increasing facility-based births in PNG. A greater understanding of the care experience as a key component of quality care is needed and any quality improvement initiatives must include the user experience as a key outcome measure.